Development of functionality principles for the automated data transmission system through wireless communication channels to ensure information protection - Yevseiev, Serhii; Milevskyi, Stanislav; Sokol, Vladyslav; Yemanov, Vladyslav; Volobuiev, Anatolii; Dakova, Larysa; Brailovskyi, Mykola; Rahimova, Irada; Kravchenko, Vladyslav; Cherniavskiy, Oleg (Eastern-European Journal of Enterprise Technologies, 2024)
The development of data transmission systems based on wireless radio communication channels allowed the construction of fundamentally new networks – mesh networks, which are used not only in smart technologies, but are the basis for the construction of cyber-physical and socio-cyber-physical systems (objects of critical infrastructure). The object is the process of ensuring reliable and secure data transmission based on the use of wireless radio communication channels. A mathematical model of information resources protection system functioning is proposed to ensure the signs of immunity and security of the automated data transmission system. To identify threats, a unified classifier and flow state estimation technique are used, which take into account the hybridity and synergy of targeted (mixed) attacks on communication channels. The critical points of the infrastructure elements, as well as the information that circulates and/or is stored, are determined. The assessment of compliance with the regulators’ requirements, both international and state regulatory acts, and the presence and ability of the security system elements to ensure the required level of infrastructure elements protection is taken into account. The proposed approach allows to determine: coefficients of information and internal availability of a wireless radio communication channel, the vector potential of the lagging magnetic field as a result of data transmission work. When evaluating the coefficient of a wireless radio communication channel internal availability, it is proposed to take into account coherent reception of the signal. At the same time, the immunity factor of the wireless radio communication channel is much higher than 1, which provides sufficient protection of information. A technical solution is proposed that will allow the level of confidentiality, integrity, authenticity and reliability of a wireless radio communication channel to approach 100 %The development of data transmission systems based on wireless radio communication channels allowed the construction of fundamentally new networks – mesh networks, which are used not only in smart technologies, but are the basis for the construction of cyber-physical and socio-cyber-physical systems (objects of critical infrastructure). The object is the process of ensuring reliable and secure data transmission based on the use of wireless radio communication channels. A mathematical model of information resources protection system functioning is proposed to ensure the signs of immunity and security of the automated data transmission system. To identify threats, a unified classifier and flow state estimation technique are used, which take into account the hybridity and synergy of targeted (mixed) attacks on communication channels. The critical points of the infrastructure elements, as well as the information that circulates and/or is stored, are determined. The assessment of compliance with the regulators’ requirements, both international and state regulatory acts, and the presence and ability of the security system elements to ensure the required level of infrastructure elements protection is taken into account. The proposed approach allows to determine: coefficients of information and internal availability of a wireless radio communication channel, the vector potential of the lagging magnetic field as a result of data transmission work. When evaluating the coefficient of a wireless radio communication channel internal availability, it is proposed to take into account coherent reception of the signal. At the same time, the immunity factor of the wireless radio communication channel is much higher than 1, which provides sufficient protection of information. A technical solution is proposed that will allow the level of confidentiality, integrity, authenticity and reliability of a wireless radio communication channel to approach 100 %